Hypothalamic-pituitary-adrenal axis activity and cognition in major depression: The role of remission status. (February 2017) - Salvat-Pujol, Neus; Labad, Javier; Urretavizcaya, Mikel; de Arriba-Arnau, Aida; Segalàs, Cinto; Real, Eva; Ferrer, Alex; Crespo, José M.; Jiménez-Murcia, Susana; Soriano-Mas, Carles; Menchón, José M.; Soria, Virginia
Highlights: We explore the role of remission status and HPA axis on cognition in MDD. Cortisol awakening response, cortisol diurnal slope, and DST were analyzed. Remission moderates the association between cortisol diurnal slope and cognitive performance. Abstract: Objectives: Neuropsychological deficits and hypothalamic-pituitary-adrenal (HPA) axis dysfunction have been described in major depressive disorder (MDD). We conducted an exploratory study to investigate the role of remission status in the relationship between HPA axis and cognition in MDD. Methods: Ninety-seven MDD patients (44 remitted, 53 non-remitted) and 97 healthy controls (HC) were evaluated. We measured verbal and visual memory, working memory, processing speed, attention, and executive function. Three HPA axis measures were assessed: cortisol awakening response (CAR), diurnal cortisol slope, and cortisol suppression ratio with 0.25 mg of dexamethasone (DSTR). Multiple linear regression analyses were performed to study the relationship between cortisol measures and cognition while controlling for potential confounders. We conducted an overall analysis in all participants to compare both MDD-remitted and MDD non-remitted groups with respect to HC. Another analysis including MDD patients only was used to explore a moderating effect by remission status. Results: MDD patients showed poorer cognitive performance compared with HC, without significant differences between remitters and non-remitters. Cortisol measures did not differ between remitters and non-remitters. Although most HPA axis measures were not associated with cognitive dysfunction, we found significant associations between cognitive performance in MDD-remitters and cortisol measures for visual memory, processing speed and executive function. A significant moderating effect for remission status was found between cortisol diurnal slope (but neither CAR nor DSTR) and performance in processing speed or executive function. Conclusions: Remission status in MDD appears to moderate the association between some cognitive domains (processing speed and executive function) and HPA axis activity.